The Routledge handbook of French politics and culture
1 online resource.
Keywords: "The Routledge Handbook of French Politics and Culture provides a detailed survey of the highly differentiated field of research on French politics, society and culture across the social sciences and humanities. The handbook includes contributions from the most eminent authors in their respective fields who bring their authority to bear on the task of outlining the current state-of-the art research in French Studies across disciplinary boundaries. As such, it represents an innovative as well as an authoritative survey of the field, representing an opportunity for a critical examination of the contrasts and the continuities in methodological and disciplinary orientations in a single volume. The Routledge Handbook of French Politics and Culture will be essential reading and an authoritative reference for scholars, students, researchers and practitioners involved in, and actively concerned about, research on French politics, society and culture"--